The Herd Dynamics Model (HDM) component of the Linked Economic and Animal Systems (LEAS) model, a tool for or policy analysis on livestock management in Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2021)
The model, developed in the context of the Feed the Future Innovation Lab for Livestock Systems, was documented in a Discussion Paper in 2021.